Genome Sequence of Bacillus cereus Group Phage SalinJah - Erill, Ivan (Genome Announc, 2016)
The double-stranded DNA (dsDNA) Myoviridae Bacillus cereus group bacteriophage SalinJah was isolated from soil collected in Gyeonggi-do, South Korea. SalinJah, a cluster C phage with a broad host range, suggests the need to create a new subcluster with SalinJah and Helga as founding members.